Persepsi Guru Terhadap Pusat Kegiatan Guru (PKG) - Mohamad Fauzi, Ahmad (1997)
The setting up of the Teacher Centre is an important step towards preparing the infrastructure to upgrade the educational qualities in schools. Hence, it has been planned to equip teachers to face problem and new requirement in accordance to changes in educational field. Even so, educationists criticize that Teacher Centre nowdays has not been fully utilised. So, the aim of this research is to look into the teachers perception towards Teacher Centres related to these critics. This research comprises the qualitative and quantitative methods. It involves the descriptive and inference analysis. A total of 341 respondents from 54 schools (38 primary schools and 16 secondary schools) took part in this survey. They represent 5 Teacher Centres. The survey carried out shows positive, strong and significance relations between teachers perceptions towards Teacher Centres with a) The enviroment and infrastructures. b) Teachers attitude. c) Courses / service training factor and d) Educational administration factors. Besides, the demographic factors had been carried out descriptively. It shows that the distance is not the key factor to teachers to be actively involved at the Teacher Centres. Based on this outcome, several suggestions to upgrade the involvement of teachers at the Teacher Centres will be submitted to the management authority for further actions.